Associations of domestic hard water metrics with the risk of gout incidence and recurrence - Sitong Wei; Jie Zhang; Shaoguang Ren; Dongqing Ye; Xinyu Fang (PLoS ONE, 2025)
Background Accumulating evidence suggests that domestic hard water is linked to health outcomes, but whether there is a potential association with gout is unknown.To examine the association between domestic hard water and gout incidence and recurrence in adults aged 40–69 years from the UK Biobank. Methods We analyzed a cohort of 448,510 participants free of gout at baseline (2006–2010) for incidence analysis and 7,231 participants with prevalent gout for recurrence. Domestic water hardness data were obtained from local water supply companies across England, Wales and Scotland in 2005 and 2013. Cox proportional hazard models were used to assess the association between water hardness and both gout incidence and recurrence. Additionally, the Cochran Armitage test was used to examine the linear trend and restricted cubic splines assessing nonlinear relationships. Results During a median follow-up of 13.29 years, 6,521 incident events were recorded, and at a median 12.40 years, 519 gout recurrence events were identified. For incidence, compared with individuals exposed to 0–60 mg/L, the HRs (95% CIs) for the incidence of gout in the other three grades were 1.12 (1.05–1.19), 1.16 (1.05–1.29) and 1.18 (1.11–1.25), respectively. Each additional 50 mg/L of CaCO3, Ca and Mg increased gout risk (HRs [95% CIs] were 1.04 [1.03–1.05], 1.17 [1.13-1.20] and 1.99 [1.46–2.71], respectively). In addition, CaCO3, Ca and Mg demonstrated the nonlinear relationship with gout incidence (all p for nonlinearity<0.05). For recurrence, each additional 50 mg/L of Mg increased gout recurrence risk (HRs [95% CIs] was 2.97 [1.11–7.97]). And linear trend test shown was significant for Mg (P for trend = 0.03026). Conclusions The results revealed that exposure to hard water characterized by higher concentration levels of CaCO3, Ca and Mg might increase the risk of gout incidence. Moreover, individuals who are subjected to higher Mg concentrations might increase the risk of gout recurrence.